Global economic prospects a fragile recovery - Ohnsorge, Franziska; Kose, M. Ayhan (World Bank Group, 2017)
Global outlook : a fragile recovery -- Special focus 1 : Debt dynamics in emerging market and developing economies : time to act? -- Special focus 2 : Arm's-length trade : a source of post-crisis trade weakness -- Regional outlooks
Includes bibliographical references
Keywords: Economic development; Finance -- Developing countries